New venture creation an innovator's guide to entrepreneurship - Meyer, Marc H. (SAGE, 2014)
The authors establish innovation as a necessary first step before writing a business plan or developing a financial model. Focussing on high-technology ventures, this insightful guide is devoted to helping students understand how innovation works and how to incorporate it into their process of conceptualizing and implementing their business idea.